Conversor CA/CC de único estágio isolado em alta frequência operando sob ZVS no lado primário - Silva, Bruno Alves Sousa da (2019)
This work proposes the study and development of a high frequency isolated single stage CA/CC converter operating under zero voltage switching (ZVS) on the primary side. The proposed converter is based on the dual active bridge (DAB) associated with the three state switching cell (CC3E), having a structure that can be modularized and applied at high voltages operating as a power factor correction single stage rectifier. A qualitative analysis is performed, which shows the modulation technique as well as the control strategy necessary for correct operation of the converter. Subsequently, a quantitative analysis of the power flow is performed through the complete model of the transformer voltages and current. The sizing of the converter controllers is also performed using the pole and zero allocation method through the MATLAB sisotool. Finally, the study is validated through simulation and experimental prototype results with 1kW. The topology is capable of operating with power factor 0.98, low THD (8.5%), 91% efficiency and ZVS soft switching on the primary side switches.